DETERMINANT FACTORS OF DROP OUT (DO) AMONG MULTI DRUGS RESISTANCE TUBERCULOSIS (MDR TB) PATIENTS AT JAKARTA PROVINCE IN 2011 TO 2015 - Farihatun, Sitti; Machmud, Putri Bungsu (Indonesian Journal of Tropical and Infectious Disease, 2018)
The prevalence of Drop out (DO) among Multi Drugs Resistant Tuberculosis (MDR TB) patients increases every year in Jakarta Province. The latest data of 2016 contains 367 drug resistant TB patients and 78 patients (21.2%) were DO. This study was aimed to analyze the determinant factors of Drop Out (DO) among MDR TB patients in Jakarta Province between 2011 to 2015 based on risk factors of age, sex, HIV status, sputum test, type of patient, number of previous treatments and number of drugs resistance. This study was used secondary data that source from cohort registration e-TB Manager from DKI Jakarta Health Office with total 516 samples. The design study was an observational cross sectional quantitative study. DO is a condition of patients who have been treated and drop out of treatment for 2 consecutive months or more. The crude prevalence of DO among MDR TB patients was 44.6%. Trend of DO among MDR TB was increased since 2011 to 2015. There was a further increase more than 10% in every year. The proportion of DO among MDR TB in Jakarta was more than 64 years old (63.6%), male (47.3%), patients with status HIV negative (44.9%), patients that never or ever consumed drugs less than 1 month (61.2%), and patients with >2 drugs resistance (45.7%). The results of this study indicated that proportion of DO among MDR TB patients at Jakarta Province in 2011-2015 was high. Therefore, it is necessary efforts that can decrease DO cases among MDR TB patients. This study was expected to be a reference for Jakarta Province Health Office in implement P2TB Program implementation and reach target precisely.